Everyday Fragments on the Ceiling of Room 407: An Open Narrative Inquiry Space. (June 2015) - Bramwell-Davis, Prunella; Filer, Jan; Maddern, Lynn; Nolan Miljevic, Jelena; Nymanhall, Sarah; Porter, Sue; Pyrsou, Bubukee; Reed, Malcolm; Sakellariadis, Artemi; Speedy, Jane; Styles, Peggy; Wilson Vasquez, Goya
Jane Speedy was leading the community of scholars in the "open space" session for March 2014 in Room 407. The Narrative Inquiry Centre held an "open space" session every month on the fourth floor of the Graduate School of Education. In "open space" sessions, one scholar led with exemplars of work that was troubling them/that they were troubling, after which others contributed their thoughts/comments and writing. Jane Speedy's recent stroke had reduced/distilled/extended her writing into fragments. Her colleagues followed/responded with fragments of their own and thus this text was collaboratively written, in real time, on March 3, 2014.